Conflitos e movimentos ambientais em torno dos megaprojetos do “Corredor Interoceânico” na região Istmo de Tehuantepec e o “Trem Maia” na Península de Yucatán, México no âmbito do Espaço global para a expansão do capital transnacional que abrange o Projeto Mesoamérica - CONTRERAS, Marcela de Lourdes (2023)
In this research we analyze the environmental conflicts around two important projects for the current Mexican government: the Interoceanic Corridor and the Mayan Train. Those conflicts are framed in the theoretical proposal of William Robinson‟s global capitalism because it allows studying the articulation of several aspects: 1) The relationship among global, national and local processes, reaching the personal if we think about the constructions of a collective subject that fights against the advance of transnational capital; 2) The mega-projects around the Mexican government‟s proposal to modernize the train on the Mexican isthmus or build a new train in the territory of 5 states in the southeast of Mexico. These mega-projects are ports, airports, industrial parks; exploration of minerals, oil and gas; wind and solar parks, tourist mega projects, real state, monoculture and livestock; 3) The geographic reconfiguration of capital in the stage of globalization in capitalism that began in the 1970s, which is expressed in the emergence of Global Spaces for the Expansion of Transnational Capital, Specific Zones of Intense Accumulation and Specific Zones of Intense Social Conflict.